Design and development of a hydrogel formulation with nanoparticles for the treatment of glioblastoma multiforme - Cardoso Dos Santos, Luiza Erthal (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2021)
Glioblastoma multiforme (GBM) is the most aggressive form of brain tumours. GBM treatment is challenging because tumours are highly invasive and it is difficult to achieve effective therapeutic doses of drugs into the brain. Indeed, the Blood Brain Barrier (BBB) impairs most of the anti-cancer drugs to reach the tumour site. To overcome this problem, different drug delivery methods, such as the direct delivery of drugs into the brain after tumour removal surgery, have been proposed. Biomaterials are in the front line of the research focus for new treatment options. Especially, biocompatible polymers have been proposed in hydrogel-based formulations aiming at injectable and localized therapies. These formulations can comprise chemotherapeutic drugs, nanoparticles, cells, nucleic acids, and diagnostic agents. In this thesis, a hydrogel-based formulation containing free drug and drug-loaded stimuli-responsive nanoparticles was developed and tested for the treatment of GBM. Specifically, in Chapter 2 a detailed description of the materials and methods used in this work is presented. In Chapter 3, the first specific objective was the synthesis and characterization of the stimuli-responsive mesoporous silica nanoparticle capped with polyethylene glycol (MSN-PEG). This was followed by the evaluation of two loaded chemotherapeutic drugs, temozolomide (TMZ) and paclitaxel (PTX) concerning the loading capacity, release profile and in vitro effect on U-87 GBM cells and healthy neurons. In addition, the stability of the nanoparticles was analysed to support the interpretation of all these data. In Chapter 4, three gels (two thermoresponsive and one chemically crosslinked) were evaluated for the combination with the nanoparticle with or without the stimuli-responsive modification. The release profile of these nanoparticles and free drugs (temozolomide, paclitaxel and carmustine) from the gels was thoroughly analysed to increase the understanding on the behaviour of the combination as a drug delivery system. This shed light on the promising materials to be used as the delivery platform for the nanoparticles developed on Chapter 3. Moreover, gel degradation was also evaluated. Through a step by step screening process, the crosslinked (CX) hydrogel was selected to compose the final formulation (GlioGel) together with free TMZ and PTX-loaded nanoparticles. In Chapter 5, the efficacy of the combination therapy was evaluated in a 3D in vitro model and the final formulation was implanted in vivo in an animal model of GBM. We used tumour spheroids as a 3D platform to evaluate the effect of the formulation in vitro regarding cytotoxicity and nanoparticles penetration. In addition, the formulation combining free TMZ and PTX-loaded MSN-PEG into the CX hydrogel was implanted in U-87 tumour-bearing mice after resection surgery to evaluate treatment efficacy in vivo. Finally, Chapter 6 is a general discussion of the research developed in this project, including the main findings of each part of the work and future research that can be conducted based on these project findings. In conclusion, a hydrogel-based formulation loaded with free chemotherapeutics and loaded nanoparticles was developed. In vivo results showed efficacy against GBM tumours after surgical resection in mice. Therefore, the GlioGel formulation is a viable option to treat GBM and improve the current chemotherapy outcomes in those patients.
APPROVED
Keywords: Glioblastoma multiforme; Injectable hydrogels; Nanoparticles; Chemotherapy; Thermo-responsive polymers